Application of Predictive Nursing Reduces Psychiatric Complications in ICU Patients after Neurosurgery - Qiong LIU; Hui ZHU (Tehran University of Medical Sciences, 2016)
Background: Our aim was to investigate the effects of clinical application of perioperative predictive nursing on reducing psychiatric complications in Intensive Care Unit (ICU) patients after neurosurgery. Methods: A total of 129 patients who underwent neurosurgery and received intensive care were enrolled in our study from February 2013 to February 2014. These patients were divided into two groups: the experimental group (n=68) receiving predictive nursing before and after operation, and the control group (n=61) with general nursing. Clinical data including length of ICU stay, duration of the patients' psychiatric symptoms, form and incidence of adverse events, and patient satisfaction ratings were recorded, and their differences between the two groups were analyzed. Results: The duration of psychiatric symptoms and the length of ICU stay for patients in the experimental group were significantly shorter than those in the control group (P<0.05). The incidence of adverse events and psychiatric symptoms, such as sensory and intuition disturbance, thought disturbance, emotional disorder, and consciousness disorder, in the experimental group was significantly lower than that in the control group (P<0.05). Patient satisfaction ratings were significantly higher in the experimental group than those in the control group (P<0.05). Conclusion: Application of predictive nursing on ICU patients who undergo neurosurgery could effectively reduce the incidence of psychiatric symptoms as well as other adverse events. Our study provided clinical evidences to encourage predictive nursing in routine settings for patients in critical conditions.